Menggaungkan Pendekatan Ekologis dalam Historiografi Perkotaan di Indonesia Pasca Reformasi - Ridhoi, Ronal (Perkumpulan Program Studi Sejarah Se-Indonesia, 2023)
Urban historiographical studies after the Reformation tend to make a significant changes. From the previous question about socio-economic problems in rural areas, then questioned daily life in urban areas. This paper tries to show that there are other approach on the urban history writing in Indonesia. By perusing some books and articles (bibliographical research) related to urban historiography before and after the Reformation period, the author tries to narrate new ideas on urban historiography. This paper shows that urban historiography produced after the Reformation shows a trend of change towards environmental problems in urban areas. This is due to the trend of post-reform environmental problems and climate crises being highlighted by academics. This paper shows also that ecological approach on the urban history research is a new field that should be explored further.